Synthesis, Characterization and Photodynamic Activity against Bladder Cancer Cells of Novel Triazole-Porphyrin Derivatives - Gomes, Ana T. P. C. (2020)
Novel triazole-porphyrin derivatives (TZ-PORs) were synthesized through the Heck reaction and then incorporated into polyvinylpyrrolidone (PVP) micelles. After verifying that this incorporation did not compromise the photophysical and chemical features of TZ-PORs as photosensitizers, the phototoxicity of the formulations towards cancer cells was screened. Biological studies show high photodynamic activity of all PVP-TZ-POR formulations against a bladder cancer cell line with a particular highlight to PVP-TZ-POR 7e and 7f that are able to significantly reduce HT-1376 cell viability, while they had no effect on control ARPE-19 cells.